Global, regional, and national burden of 10 digestive diseases in 204 countries and territories from 1990 to 2019 - Wang, Rui; Li, Zhaoqi; Liu, Shaojun; Zhang, Decai (Frontiers in Public Health, 2023)
Background: Digestive diseases are very common worldwide and account for considerable health care use and expenditures. However, there are no global population-based estimates of the disease burden and temporal trend of digestive diseases. Methods: Annual case numbers, age-standardised rates of prevalence, incidence, death, and disability-adjusted life-years (DALYs), and their estimated annual percentage changes (EAPCs) for digestive diseases between 1990 and 2019 were derived from the Global Burden of Disease, Injuries, and Risk Factors Study (GBD) 2019. The association between digestive disease burden and the sociodemographic index (SDI) was investigated. We also calculated DALYs attributable to risk factors that had evidence of causation with digestive diseases. Results: Globally, in 2019, there were 88.99 million DALYs due to digestive diseases (3.51% of global DALYs). Digestive diseases were the 13th leading cause of DALYs globally in 2019. Global digestive disease DALYs were highest in the middle SDI quintile and in South Asia and were higher in males than females in 2019. Cirrhosis and other chronic liver diseases constituted the highest proportion of categorised digestive disease DALY burdens globally. From 1990 to 2019, the global age-standardised DALY rate of digestive diseases decreased from 1570.35 in 1990 to 1096.99 in 2019 per 100000 population, with the EAPC being -1.32 (95% confidence interval [CI] -1.36 to -1.27). In 2019, the largest contributor to digestive disease DALYs at the global level, for both sexes, was alcohol use. Conclusion: The results of this systematic analysis suggest that the global burden of digestive diseases is substantial and varies markedly according to age, sex, SDI, and geographical region. These results provide comprehensive and comparable estimates that can potentially inform efforts towards digestive disease control worldwide.